The Ess/Type VII secretion system of Staphylococcus aureus shows unexpected genetic diversity - Warne, Ben (BMC Genomics, 2016)
BACKGROUND: Type VII protein secretion (T7SS) is a specialised system for excreting extracellular proteins across bacterial cell membranes and has been associated with virulence in Staphylococcus aureus. The genetic diversity of the ess locus, which encodes the T7SS, and the functions of proteins encoded within it are poorly understood. RESULTS: We used whole genome sequence data from 153 isolates representative of the diversity of the species to investigate the genetic variability of T7SS across S. aureus. The ess loci were found to comprise of four distinct modules based on gene content and relative conservation. Modules 1 and 4, comprising of the 5’ and 3’ modules of the ess locus, contained the most conserved clusters of genes across the species. Module 1 contained genes encoding the secreted protein EsxA, and the EsaAB and EssAB components of the T7SS machinery, and Module 4 contained two functionally uncharacterized conserved membrane proteins. Across the species four variants of Module 2 were identified containing the essC gene, each of which was associated with a specific group of downstream genes. The most diverse module of the ess locus was Module 3 comprising a highly variable arrangement of hypothetical proteins. RNA-Seq was performed on representatives of the four Module 2 variants and demonstrated strain-specific differences in the levels of transcription in the conserved Module 1 components and transcriptional linkage Module 2, and provided evidence of the expression of genes the variable regions of the ess loci. CONCLUSIONS: The ess locus of S. aureus exhibits modularity and organisational variation across the species and transcriptional variation. In silico analysis of ess loci encoded hypothetical proteins identified potential novel secreted substrates for the T7SS. The considerable variety in operon arrangement between otherwise closely related isolates provides strong evidence for recombination at this locus. Comparison of these recombination regions with each other, and with the genomes of other Staphylococcal species, failed to identify evidence of intra- and inter-species recombination, however the analysis identified a novel T7SS in another pathogenic staphylococci, Staphylococcus lugdunensis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2426-7) contains supplementary material, which is available to authorized users.